Association between smoking and hand dermatitis – a systematic review and meta‐analysis. (4th February 2015) - Lukács, J.; Schliemann, S.; Elsner, P.
Abstract Tobacco smoking is known to influence various inflammatory skin diseases. A systematic review with a meta‐analysis was conducted to analyse a possible association between the lifestyle factor tobacco smoking and hand dermatitis. We performed a systematic review using the MEDLINE, Embase and Cochrane Central Register databases. Our search was limited to English and German language, human‐subject studies published between January 1, 1980 and December 31, 2013. A total of 43 articles were identified from the initial search, and after taking into account exclusion criteria, only three studies remained investigating the risk factors for hand eczema in the general and in high‐risk populations (e.g. bakers, hairdressers, dental technicians). The extracted data were pooled and analysed by standard statistical methods. The studies meeting inclusion criteria consisted of one cohort study and two cross‐sectional studies based on a total of 4.113 subjects with hand dermatitis and 34.875 subjects without hand dermatitis. While one of the studies had reported a significant association between hand dermatitis and smoking, the meta‐analysis did not confirm this finding (OR 0.99; 95% CI 0.88–1.11). However, heterogeneity across studies was high (I2 = 72%). Our meta‐analysis did not show tobacco smoking to be a risk factor for hand dermatitis. However, these results depend mainly on two large studies from one country. From present data, it cannot be excluded that smoking may influence the course of hand dermatitis. Even though smoking does not seem to be associated with hand dermatitis, it may still negatively influence the course of the disease.